Discussing The Love of Eve and Adam by Expressing the God’s Master Plan for the Human in the Selected Novel The Partly Fortunate: Exploring the Themes of Love and Divine Plan for Humanity in Paradise Lost (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Love is one of the Christian God's most important attributes, and Heavenly love additionally becomes the overwhelming focus from the get-go in the poem as the angels ceaselessly worship God and cooperative with one another in euphoria, and the Son offers himself as a sacrifice for humankind out of love for them. At that point when Adam and Eve are made, the poem partly moves its concentration to mortal love and the possibility of marriage. Joyce's utilization of the Felix culpa in Finnegan’s Wake likewise demonstrates the impact of Milton upon his work. Heaven Lost finishes up with an astonished Adam who has been demonstrated the eventual fate of the world, culminating in the redemption of wrongdoing by Christ. This paper points in considering the theme of love and the fall of humankind is partly fortunate in Paradise Lost Book I. It studies love of Adam towards Eve and its consequences and the fortune and the divine love gives over Mankind. The fall eventually reveals God's plan for the Mankind.